Musykilah al-Iâ€™tidÄ ala al-MahÄrim fÄ« Malaysia: TahqÄ«qu Ahammiyati QÄ«mah al-Istiâ€™dzÄn fi al-IslÄm wa JawÄnibuhÄ al-Tarbawiyyah - Binti Ali, Nurul Badriyah; Elatrash, Radwan Jamal (IAIN Samarinda, 2017)
The problem of incest, including its incidence among Muslim societies, is one of the major legal cases faced by lawyers in Malaysia. Incest cases are often hidden because they are considered a disgrace of the family and society that cannot be forgiven. As a result, justice for the victims is difficult to enforce, and the case continues to occur because the law is considered not able to ensnare the perpetrators (deterrence effect). One researcher found that among the causes of incest is the ignorance of Islamic law in everyday life, especially in applying the values of